Empirical Analysis of E-Consumer Laws and Way Forward for Better Protection - Sarabdeen, Jawahitha (Journal of Posthumanism, 2025)
E-consumer laws are in infancy though e-commerce has matured in Malaysia. The traditional laws passed decades ago are still used even for e-commerce disputes and dispute resolutions. The article reviewed the literature on e-consumer protection and interviewed experts to see the applicability of the current law to protect consumers in e-commerce. The interview results revealed that the Contract Law, Sale of Goods Act, the Consumer Protection Act, the law on negligent liability, and laws related to courts’ jurisdiction and execution of judgment need to be amended for better protection. The research finding has policy implications. The research suggested the areas where amendments to the existing legislation and laws should be needed and the reason for such amendments. The research contribution is significant as no research collected the opinion of experts in the area to suggest changes to the laws and regulations so that consumers in e-commerce could be better protected.